An enhanced online learning environment in the time of COVID-19 - Ouf, Shimaa (Informatica, 2021)
Abstract: The coronavirus has resulted in educational and universities shut all across the globe. There are over 1.2 billion students in 191 countries are out of the educational institutions all over the world. The world is now transforming training, learning, and work online to achieve the safety of workers, students, and educators, reduce total fatalities from the disease, and flatten the infection curve. To make the shifting to online learning easy, manageable, secure, and effective, this paper analyzes the challenges of the current learning environment and proposes architecture to solve these challenges. The learning environments face challenges in securing their private data, tracking student's behavior, the low quality of the learning process, and centralized authority. Educational institutions need to develop efficient, effective, transparent, immutable, and secure learning environments. A detailed study, which introduces research papers, which apply blockchain within the learning process, is discussed. Most of these studies focus on improving the learning process by using blockchain technology ignored other important technologies like the semantic web. The integration of the semantic web with blockchain will create a semantic blockchain. The Sematic blockchain will help educational institutions to enhance their learning process in transit and storage, improving student satisfaction and trust through transparency in a decentralized manner. It is considered a key technology of the next generation of e-learning systems. In this paper, the proposed model for improving the learning process based on a semantic blockchain is introduced.